2013
DOI: 10.1186/1471-2334-13-196
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in process of care and outcome in patients requiring intensive care unit admission for community acquired pneumonia

Abstract: BackgroundThe present study was performed to assess the prognosis of patients admitted to the intensive care unit (ICU) for community acquired pneumonia (CAP) after implementation of new processes of care.MethodsTwo groups of patients with CAP were admitted to a 16-bed multidisciplinary ICU in an urban teaching hospital during two different periods: the years 1995–2000, corresponding to the historical group; and 2005–2010, corresponding to the intervention group. New therapeutic procedures were implemented dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
1
11
0
3
Order By: Relevance
“…Other studies show diverging results in regard to the temporal outcomes of patients with severe CAP. Using a beforeafter design, Georges et al compared the outcomes of patients with severe CAP in the periods of 1995e2000 and 2005e2010 [2]. Processes of care in compliance with some of the 2004 Surviving Sepsis Guidelines recommendations [6] were implemented in their institution before the 2005e2010 period.…”
Section: Temporal Assessment Of Severe Cap In Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies show diverging results in regard to the temporal outcomes of patients with severe CAP. Using a beforeafter design, Georges et al compared the outcomes of patients with severe CAP in the periods of 1995e2000 and 2005e2010 [2]. Processes of care in compliance with some of the 2004 Surviving Sepsis Guidelines recommendations [6] were implemented in their institution before the 2005e2010 period.…”
Section: Temporal Assessment Of Severe Cap In Other Studiesmentioning
confidence: 99%
“…The generalizability of these findings is Figure 1 In-hospital mortality percentage and 95% confidence interval according to time period in patients with severe community-acquired pneumonia. limited because the study was carried out in a single center [2]. Using a large administrative database, Woodhead et al evaluated the outcomes of 17,869 patients with CAP that required ICU admission during the periods of 1995e1999 and 2000e2004.…”
Section: Temporal Assessment Of Severe Cap In Other Studiesmentioning
confidence: 99%
“…La pneumonie communautaire grave (PCG) est la première cause de sepsis sévère et de choc septique rencontrée aux urgences [1]. Près de la moitié des patients présentant une PCG nécessite une hospitalisation en réanimation où la mortalité varie de 15 à 40 % selon les séries rapportées [2][3][4]. Les études épidémiologiques permettent d'actualiser régulièrement les agents microbiologiques responsables des PCG [5][6][7].…”
Section: Abstract Severe Community Acquired Pneumonia · Microbial Diaunclassified
“…One study,10 which compared patients with CAP admitted to the intensive care unit in two periods (1995–2000 and 2005–2010), suggests that the decrease in mortality observed may be related to the follow-up of a sepsis management bundle derived from the Surviving Sepsis Campaign. In severe pneumococcal CAP, Gattarello et al 11 showed a decreased mortality with time.…”
mentioning
confidence: 99%